(untitled) (Research, Society and Development, 2020)
In research in the scope of Mathematics Education, it is possible to notice works that point out the potential of the history of mathematics for teacher training. As we can observe, the importance of history rests on the fact that it provides some knowledge necessary for the teacher’s work, for example, there are those that refer to the content to be taught, because history can indicate the process of knowledge construction. In the field of education, knowledge has been used to think about teacher training from the perspective of some scholars, such as Shulman (1986, 1987) and Tardif (2000, 2002). In this sense, it is noted that the theoretical basis on knowledge can support research that seeks to articulate the history of mathematics and teacher education. In this perspective, the objective was to present a survey of research from the last 5 years that deal with teacher education based on an approximation between the history of mathematics and the teaching knowledge. For that, we worked under the methodological support of the investigation method of a systematic literature review. The cataloged and analyzed research revealed that the work with the history of mathematics in teacher education has not been articulated and / or subsidized by the references that deal with teaching knowledge. Some research even brings considerations from authors like Lee Shulman, however they have not been explored as a theoretical framework to look at teacher education. A very incipient approach was noted, a fact that possibly minimizes the possibilities of thinking about the education of mathematics teachers.